2013
DOI: 10.5455/aim.2013.21.123-126
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Diabetic Polyneuropathy in Inpatient Care: Fasting Blood Glucose, HbA1c, Electroneuromyography and Diabetes Risk Factors

Abstract: CONFLICT OF INTEREST: NONE DECLAREDGoalThe goals of this study are to: a) determine the prevalence of diabetic polyneuropathy (DPNP) in hospitalized patients with diabetes mellitus (DM) type 2; b) determine the frequency of DPNP in hospitalized patients with type 2 DM in relation to gender, duration of diabetes, fasting blood glucose and HbA1c; c) identify the dominant DPNP symptoms and the presence of variable risk factors in hospitalized patients; and d) determine the frequency and motor nerve conduction vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
5
3
1
Order By: Relevance
“…Maximum patients (56.8%) have a DM duration for >10 years. HbA1c and longer duration of DM are strongly related with development of DPN which have been documented in a number of previous studies 9, [14][15][16][17] which demonstrates the similar pattern of HbA 1c mean value and disease duration in patients of DPN. Maximum patients (56%) of the study population have HbA1c≥ 7%.…”
Section: Clinical Severitysupporting
confidence: 70%
“…Maximum patients (56.8%) have a DM duration for >10 years. HbA1c and longer duration of DM are strongly related with development of DPN which have been documented in a number of previous studies 9, [14][15][16][17] which demonstrates the similar pattern of HbA 1c mean value and disease duration in patients of DPN. Maximum patients (56%) of the study population have HbA1c≥ 7%.…”
Section: Clinical Severitysupporting
confidence: 70%
“…These results were consistent with findings of other studies. 21,30,31 It was to be found that the peripheral neuropathy was more common in females than males which was also observed by Alam 32 but contrast to other studies. 21,22,24,33 This study also revealed a significant association of peripheral neuropathy with non-urban(rural and semi urban) residence.…”
Section: Hba 1c Categories (%)contrasting
confidence: 51%
“…This finding agrees to others 7,[16][17][18][19][20] . But Ashok et al found lower FSG and HbA1c 21 .…”
Section: Discussionsupporting
confidence: 83%